Network Monitoring System Design with Telegram Notification at SMAN 7 Bengkulu Selatan - Ede Ilham; Sastya Hendri Wibowo; Khairullah; A.R Walad Mahfuzhi (Penerbit Jurnal Indonesia, 2025)
Currently, the use of computer networks is very necessary, such as for teaching and learning activities and work. SMAl N 7 Bengkulul Selatan already has a network that is used for teaching and learning activities. Currently, the computer network in the computer laboratory of SMAl N 7 Bengkulul Selatan has 24 Computer Units. The computer network in the computer laboratory of SMAl N 7 Bengkulul Selatan does not yet have a system that can perform monitoring, so it is slow to find out the problems that occur on the network. One of the applications that performs network monitoring is lzabbix. Zabbix in performing network monitoring can send notifications to telegram. Zabbix can run on the Linux Ubuntu Server 20.04 operating system. The Linux Ubuntu Server 20.04 operating system is used because it is open source and does not require high hardware specifications. Because the Linux Ubuntu operating system runs network monitoring using Zabbix using small server resources. Zabbix can monitor problems that occur on each client and the time the problem occurs. Zabbix can also send real-time problem information to the network admin's telegram, so that the admin can easily find out the problems that occur on the computers connected to the network. In addition to the problem information sent to Telegram, it is also stored in the server log, so that the admin can see it later on the problems that occur.